Python CI/CD for the Command-Line - Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn to setup CI/CD with Github Actions for a Python Click Project Topics include: * Click * CI/CD * Github Actions * Matrix Tests in Github Actions.